2020
DOI: 10.1021/acs.jafc.0c05064
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Its Metabolites Inhibit Recombinant Human Angiotensin-Converting Enzyme 2 (ACE2) Activity

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a host receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Inhibiting the interaction between the envelope spike glycoproteins (S-proteins) of SARS-CoV-2 and ACE2 is a potential antiviral therapeutic approach, but little is known about how dietary compounds interact with ACE2. The objective of this study was to determine if flavonoids and other polyphenols with B-ring 3′,4′-hydroxylation inhibit recombinant human (rh)­ACE2 activity. rhACE2 activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 47 publications
1
82
0
Order By: Relevance
“…Additional recent studies report that early, but not late phase ( Mongardon et al, 2020 ), low-dose corticosteroids decrease mortality and improve COVID-19 clinical outcomes ( Ji et al, 2020 ). However, another recent study indicates that corticosteroid use is associated with increased mortality and delayed SARS–CoV-2 coronavirus RNA clearance in 409 COVID-19 patients ( J. Liu et al, 2020 ). While some of the meta-analyses conclude that the use of corticosteroids is associated with a higher rate of ARDS in COVID-19 patients ( Z. Yang et al, 2020 ; J. J. Y. Zhang, Lee, Ang, Leo, & Young, 2020 ), a recent randomized study of several thousands of hospitalized COVID-19 patients reports that dexamethasone reduces the mortality among those receiving invasive mechanical ventilation or oxygen ( Horby et al, 2020 ).…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 99%
“…Additional recent studies report that early, but not late phase ( Mongardon et al, 2020 ), low-dose corticosteroids decrease mortality and improve COVID-19 clinical outcomes ( Ji et al, 2020 ). However, another recent study indicates that corticosteroid use is associated with increased mortality and delayed SARS–CoV-2 coronavirus RNA clearance in 409 COVID-19 patients ( J. Liu et al, 2020 ). While some of the meta-analyses conclude that the use of corticosteroids is associated with a higher rate of ARDS in COVID-19 patients ( Z. Yang et al, 2020 ; J. J. Y. Zhang, Lee, Ang, Leo, & Young, 2020 ), a recent randomized study of several thousands of hospitalized COVID-19 patients reports that dexamethasone reduces the mortality among those receiving invasive mechanical ventilation or oxygen ( Horby et al, 2020 ).…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 99%
“…Conversely, a computational investigation evidenced it as able to bind at S protein: ACE2 receptor interface [ 73 ]. In vitro studies demonstrated that quercetin inhibited recombinant human (rh) ACE2 activity [ 74 , 75 ]. More recently, the clinical trials (NCT04468139 and NCT04377789) including quercetin, were involved in both prophylaxis and treatment of COVID-19 [ 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, free quercetin was found to have the strongest antioxidant activity, confirming the important contribution of unbound hydroxyl groups ( 49 ). Among its metabolites, free quercetin was also the most effective recombinant human angiotensin-converting enzyme (ACE) 2 inhibitor ( 50 ). Tamarixetin and isorhamnetin demonstrated a stronger inhibition of lipid peroxidation compared to quercetin ( 49 , 51 ).…”
Section: Quercetinmentioning
confidence: 99%